ESTRESSE SALINO E HÍDRICO NA GERMINAÇÃO E CRESCIMENTO INICIAL DE PLÂNTULAS DE Toona ciliata M. ROEM. var. australis - Júlio Rieger Lucchese; Marciéli Pitorini Bovolini; Marcio Alberto Hilgert; Carolina Brito Brose; Eduarda Demari Avrella; Marília Lazarotto (Ciência Florestal, 2018)
The Toona ciliata var. australis is a tree species which yields a very high-quality timber for furniture and is unaffected by Hypsipyla grandella, a pest that attacks monoculture plantations of native species similar to Toona ciliata. It has a close relationship with water availability, occurring mainly in humid forest in its natural habitat. In commercial plantations this is an important limitation to the establishment and initial growing of Toona ciliata. In the last decades, the use of Toona ciliata in commercial plantations has increased in Brazil, however, there is little knowledge about the effect of adverse environments on seed germination and early seedling growth. This study aimed to evaluate the effects of water and saline stress on germination and early seedlings growth of Toona ciliata. Osmotic solutions were prepared with, or NaCl, or PEG 6000, in the following osmotic potentials: -0.1; -0.2; -0.3; -0.4; -0.5; -0.6; -0.9; -1.2 and -1.5 MPa. For the control treatment, it was only used sterile water. The seeds were submitted to the germination test in which the germitest paper was moistened with the relative osmotic solution. The incubation was realized in a germination chamber at 25 ± 2 °C with 16 h light of photoperiod. The experimental design was completely randomized, arranged in a factorial design 2 × 10 (osmotic agent × osmotic potential and control), with four repetitions of 50 seeds each. With the reduction on the osmotic potential was observed lower germination, number of normal seedlings, fresh weight, seedling length and higher number of hard seeds, being the effect of PEG 6000 more severe. The germination and number of abnormal seedlings was higher under NaCl effect than PEG 6000. It can be concluded that germination and early seedling growth of Toona ciliata are affected by both saline and water stress, being more sensitive under water stress and with higher probability of developing abnormal seedlings under saline stress.